"Walk without feet, fly without wings, think without mind" - Osho (New Delhi, 2011)
This is no ordinary book - its secret lies behind your breath as you read. It's not the philosophy, no - not the wealth of information here, not even the useful tidbits that brighten your day. This is something else... Osho speaks about parents and their children, about trusting and creativity and surrender; he speaks on sex and responsibility and jealousy, love, enlightenment, pornography; on play and desirelessness and belief in God. And it's something else. Reading this book can be a meeting with the Master. And that is the sweetness here, not just in the words or the answers he gives. - Ma Prem Maitri
Keywords: Spiritual life